Nonlocal inverse boundary-value problem for a 2D parabolic equation with integral overdetermination condition - Azizbayov, E.I.; Mehraliyev, Y.T. (Carpathian Mathematical Publications, 2020)
This article studies a nonlocal inverse boundary-value problem for a two-dimensional second-order parabolic equation in a rectangular domain. The purpose of the article is to determine the unknown coefficient and the solution of the considered problem. To investigate the solvability of the inverse problem, we transform the original problem into some auxiliary problem with trivial boundary conditions. Using the contraction mappings principle, existence and uniqueness of the solution of an equivalent problem are proved. Further, using the equivalency, the existence and uniqueness theorem of the classical solution of the original problem is obtained.